Student engagement amid oscillating delivery methods within a South African Private Higher Education Institution during a pandemic - Kriel, Marna (The IIE, 2022)
The COVID‐19  pandemic  brought a  whole  new  dimension to  face‐to‐face Higher Education  in  South Africa through emergency measures of migrating students to Emergency Remote Learning environments  to  preserve  health  and  continue  the  academic  discourse.  In  this  Exploratory  research, the Qualitative approach focused on student engagement, personal stories and how students experienced the fluctuation between face‐to‐face and Emergency Remote platforms. Using the Community of Inquiry to inform the theoretical framework, data was collected through focus  groups  and  interviews,  through  non‐probability,  voluntary  and  spontaneous  snowball  sampling, capturing textual data, which was analysed through thematic coding. The most significant  finding  in  this  study  was  that  participants  did  not  realise  the  effect  of  the  social  presence and how much they needed social interaction, especially in a face‐to‐face context. Time management was another major theme, where students preferred having their schedules, being able to rest, and cutting down on commute and travelling costs. The emotional and psychological theme was primarily due to students being socially isolated, falling into mental health difficulties, or having to assist family members. The need for psychological support seems to go deeper than previously thought. A leniency hybrid delivery mode due was recommended for flexibility, time management, fewer time spending on commute, and limiting travelling cost.
Keywords: COVID‐19; Community of Inquiry (CoI); Teaching presence; Social presence; Cognitive presence; Emergency Remote Teaching Learning and Assessment (ERTLA); Emergency Remote Teaching (ERT), Student Engagement; Student Experience; Higher Education; Psychological support